Nanotechnologies for Intracellular Protein Delivery: Recent Progress in Inorganic and Organic Nanocarriers. Issue 6 (2nd April 2021) - Le Saux, Sarah; Aubert‐Pouëssel, Anne; Ouchait, Lyria; Mohamed, Khaled Elhady; Martineau, Pierre; Guglielmi, Laurence; Devoisselle, Jean‐Marie; Legrand, Philippe; Chopineau, Joël; Morille, Marie
Abstract: From recombinant insulin to monoclonal antibodies, proteins have become essential drugs in the therapeutic arsenal and respond to a broad spectrum of diseases. While commercially available proteins have an extracellular activity, intracellular targets can be a powerful alternative to treat many pathologies such as cancers and immune disorders, but also infectious diseases. Nevertheless, to enter the cell and reach the target organelle or molecule, therapeutic proteins have to face numerous barriers (internalization, endosomal escape, and cytoplasm trafficking). In view of the fragile nature and high heterogeneity of proteins in terms of size, charge, and hydrophilic/lipophilic profile, the development of an efficient cytoplasm delivery system remains a long‐standing challenge. The discovery of several gene editing tools (Clustered Regularly Interspaced Short Palindromic Repeat (CRISPR), involving caspase 9 (Cas9) protein (CRISPRCas9), transcription activator‐like effectors (TALEs) or other zinc‐finger proteins (ZFPs)) has particularly boosted this research field in the last decade. Among delivery systems that can be used in vivo, some synthetic nanovectors offer interesting opportunities. In this review, the authors describe the most recent progress in the development of inorganic (silica, gold, phosphate, metal–organic framework, carbon nanoparticles) as well as organic (polymer, lipid) nanoparticles, both applied to intracellular protein delivery. Abstract : Intracellular protein delivery can be a powerful alternative to treat many pathologies. To enter the cell and reach the target organelle or molecule, an efficient protein delivery system is required. This review describes recent progress in the development of inorganic (silica, gold, phosphate, metal–organic framework, carbon nanoparticles) as well as organic (polymer, lipid) nanoparticles applied to intracellular protein delivery.